The Efficacy of Aqueous and Alcoholic Extracts of Yas Plant (Eriobotrya Japonica) Leaves on Mortality of Larval and Adult Stages of Rusty Flour Beetle (Tribolium Castaneum) - Abbas, Zainab M.; Shandookh, Fatima Kareem (American Journal of Biology and Natural Sciences, 2025)
The increasing demand for sustainable pest management strategies has led to a growing interest in the development and application of natural bioactive compounds as alternatives to synthetic insecticides. This study evaluates the insecticidal potential of aqueous and alcoholic leaf extracts derived from Eriobotrya japonica (commonly known as Yas plant or loquat) against both larval and adult stages of the rusty flour beetle, Tribolium castaneum —a major pest of stored grains and cereal products. The investigation employed probit analysis , using two complementary statistical approaches: Finney’s method assuming a lognormal distribution , and least squares probit regression based on a normal distribution , to estimate lethal dose thresholds (LD₁₀, LD₅₀, LD₉₀, LD₁₀₀) across two exposure durations (24 and 48 hours). Results revealed that adult beetles exposed for 48 hours exhibited the highest sensitivity to the stimulus, with an LD₅₀ value of 4.7367 units (95% confidence interval: 3.9561–5.8424). In contrast, larvae showed significantly greater tolerance , particularly after 24-hour exposure, where mortality rates did not increase appreciably even at higher concentrations. Notably, extending the exposure period to 48 hours did not markedly enhance larval mortality, suggesting intrinsic physiological resistance mechanisms such as reduced cuticle permeability, enhanced detoxification pathways, or sequestration of toxic compounds. Model fit was statistically acceptable across all experimental groups, as evidenced by non-significant chi-square tests and high p-values (>0.8) , indicating strong agreement between observed and expected responses. Both analytical methods yielded consistent results, reinforcing the reliability of the estimated lethal doses. These findings demonstrate that Eriobotrya japonica leaf extracts exhibit time- and dose-dependent toxicity , particularly effective against adult T. castaneum . The observed differential susceptibility among developmental stages underscores the importance of tailoring application strategies based on life cycle dynamics. Given biodegradability low mammalian toxicity and demonstrated efficacy E. japonica holds promise as a botanical insecticide in integrated pest management (IPM) programs aimed at reducing reliance on chemical pesticides. This study contributes to the expanding body of research on plant-derived insecticides provides a quantitative framework for evaluating biological responses to external stimuli offering practical insights for sustainable pest control in agricultural and storages systems.